(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores Arabic loanwords in the Russian language that have undergone full phonetic, morphological, and semantic adaptation. Special attention is given to words that have become so deeply integrated into everyday speech that their foreign origin is no longer recognized. Through selected examples, the paper analyzes the paths through which Arabic words entered Russian—often via intermediary languages—and the transformations they experienced along the way. The aim is to demonstrate how these elements became part of the Russian lexicon and to highlight the role of historical and cultural exchange in this process.